Distances to emergency departments and non-urgent utilization of medical services: a systematic review - Uma Kelekar; Debasree Das Gupta; Nicole Theis-Mahon; Emily Fashingbauer; Boyen Huang (Taylor & Francis Group, 2024)
Background The use of Emergency Departments (EDs) for non-urgent medical conditions is a global public health concern. Objectives A systematic review, guided by a registered protocol (PROSPERO: CRD42023398674), was conducted to interpret the association between distance as a measure of healthcare access and the utilization of EDs for non-urgent care in high- and middle-income countries. Methods The search was conducted on 22 August 2023 across five databases using controlled vocabulary and natural language keywords. Eligibility criteria included studies that examined non-urgent care, and featured concepts of emergency departments, non-urgent health services and distance, reported in English. Articles and abstracts where patients were transported by ambulance/paramedic services, referred/transferred from another hospital to an ED, or those that measured distance to an ED from another health facility were excluded. The Grading of Recommendations, Assessment, Development, and Evaluations (GRADE) framework informed the quality of evidence. Results Fifteen articles met the inclusion criteria. All studies demonstrated satisfactory quality with regard to study design, conduct, analysis and presentation of results. Eight (53.3%) of the studies (1 paediatric, 4 all ages/adult, 3 ecological) found a moderate level of evidence of an inverse association between distance and ED visit volume or utilization for non-urgent medical conditions, while the remaining studies reported very low or low evidence. Conclusions Half of the studies reported non-urgent ED use to be associated with shortest distance traveled or transportation time. This finding bears implications for healthcare policies aiming to reduce ED use for non-urgent care.